African philosophy in search of identity - Masolo, D. A. (Indiana University Press, 1994)
A Kenyan philosopher surveys themes and debates in African philosophy over the last five decades. Masolo's purview includes Francophone and Anglophone philosophers in both the analytic and phenomenological traditions. -- Publisher description.
"Published in association with the International African Institute, London."
Keywords: Philosophy, African.; Africa, Sub-Saharan -- Intellectual life.; Philosophie africaine.; Afrique subsaharienne -- Vie intellectuelle.; PHILOSOPHY -- History & Surveys -- Modern.; Intellectual life; Philosophy, African; Sub-Saharan Africa; Philosophie; Afrika; Afrikaanse filosofie.; Philosophie -- Afrique -- 20e siècle.; Afrique noire -- Vie intellectuelle.; Philosophy; Africa